2022
DOI: 10.2147/nrr.s345901
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Nurses Caring Behavior with the Level of Patient Satisfaction, Harari Region, Eastern Ethiopia

Abstract: The extent to which nurses tailor their care to the patient's specific needs has a direct impact on patient health outcomes. Satisfied people will have good communication with the health professional, which results in good care and health outcome, so this study aimed to assess the association of caring behavior of nurses with the level of patient satisfaction, in public hospitals of the Harari region, Eastern Ethiopia, from March 10 to April 10, 2021. Methods: A cross-sectional study was conducted among 300 nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…The proportion of overall caring behaviour of nurses in this study was 53.3%. This finding is lower than the study conducted in Indonesia (64.7%), Gondar (68.2%), Jimma (80.3%)12 13 15 and is higher than the study conducted in Harar (51.67%) 14. The variation in result may be due to scope of study area.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The proportion of overall caring behaviour of nurses in this study was 53.3%. This finding is lower than the study conducted in Indonesia (64.7%), Gondar (68.2%), Jimma (80.3%)12 13 15 and is higher than the study conducted in Harar (51.67%) 14. The variation in result may be due to scope of study area.…”
Section: Discussioncontrasting
confidence: 67%
“…Studies done in Ethiopia showed a high amount of nurses had practiced good caring behaviour while caring for their patients, 80.3% in Jimma, 68.2% in Gondar and 51.6% in Hara 12–14. Despite this, in Ethiopia, nearly one out of every two patients was dissatisfied with their nursing service.…”
Section: Introductionmentioning
confidence: 99%
“…The executing nurse is responsible for providing direct care to patients by established standards of nursing practice. They carry out tasks such as administering medicines, treating wounds, performing simple medical procedures, and providing emotional and psychological support to patients and their families (Kibret et al, 2022). Work motivation is the force that drives a person to act, work, or achieve a specific goal (Suriyani et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, caring is an important part of nursing practice and a competence that nurses should have. Evidence shows that caring has positive effects on both patients and nurses [ 4 ], such as improved patient satisfaction with care [ 5 , 6 ] and improved job satisfaction and engagement for nurses [ 7 ]. Culture is an important factor affecting the cognition and practice of caring [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%